Використання ігрових технологій у формуванні лексичної компетентності на уроках англійської мови учнів 5-6 класів - Дрощак, Юлія Вікторівна (Чернівецький національний університет ім. Ю.Федьковича, 2024)
The Use of Game-Based Technologies in Developing Lexical Competence in English Lessons for 5th Grade Students In the context of a modern educational process oriented toward innovative approaches, effective language acquisition by middle school students has become a topic of significant interest. Game-based technologies in English language learning hold great potential for developing lexical competence, especially among 5th graders. During this period, students are actively expanding their vocabulary, learning to use words in various communicative situations, and practicing teamwork skills. Play is a natural activity for children at this age, making it a powerful tool for skill development. Research Objective: To explore and scientifically determine the specifics of applying game methods and scenarios in English language lessons in middle school. Research Object: The process of developing receptive and productive lexical skills using game-based technologies during the learning process. Research Subject: The content and system of exercises within game-based technologies for developing lexical skills in middle school. Research Tasks: - To analyze the position of game-based technologies in the methodological literature; - To characterize the main types of game-based technologies and examine their classifications; - To identify the properties, objectives, and tasks of using game-based technologies in English lessons at school; - To outline pedagogical prerequisites for using games in foreign language lessons for 5th-6th graders; - To summarize the methodology of using game-based technologies in foreign language lessons; - To analyze the impact of game-based technologies from the perspectives of both the teacher and the middle school student; 3 - To assess the effectiveness of applying game-based technologies in lessons; - To conduct an analysis of the exercise system for developing receptive and productive lexical skills in 5th-6th grade students; - To develop recommendations on the use of game-based technologies. Research Methods: To accomplish these objectives, a research methodology was developed, involving a comprehensive set of methods: bibliographic method, experimental psychological research using projective techniques and verbal tests, critical analysis and synthesis methods, as well as quantitative and qualitative data analysis methods. The practical significance of this work lies in the potential to use its core principles and findings in teaching students. This master’s thesis explores the effectiveness of using game-based technologies in teaching English to younger students. The research aims to determine how game-based technologies can contribute to enhancing the lexical competence of students in this age range. The paper examines the theoretical aspects of developing lexical competence in younger students and the principles of using game-based technologies in the educational process. Based on an analysis of pedagogical literature and the results of an original experiment, a connection is established between the use of game-based technologies and the improvement of students’ lexical competence.
Keywords: game-based technologies, lexical competence, English language, lessons, primary school, learning, effectiveness, methodology, research, application, pedagogy